Economics - Arnold, Roger A. (West, 1989)
Offering a unique blend of solid theoretical content and student accessibility, this book stands apart with its emphasis on intriguing applications that convey the prevalence of economics in everyday life. By applying economics to phenomenon that readers are familiar with and interested in, this book demonstrates like no other text how economic analysis can be applied to virtually anything of interest, thus helping the reader develop true economic intuition. Additional features include a unique active-learning format, an emphasis on developing economic analysis skills, and an outstanding visual program for exhibits and graphs. Content highlights include balanced presentation of major macro theories; a micro presentation that centers around the trilogy of objectives, constraints, and choices; thorough integration of international topics; and fully-integrated Internet features that offer hands-on exercises for exploring economics on-line. Economics.